Around the world 80 dream vacations - Stoppa, Simona (White Star Publisher, 2014)
TRAVEL & HOLIDAY GUIDES. Readers who hold this book in their hands feel as if they have booked a passage on a fabulous journey to 80 of the world's best loved destinations. The dream getaways on five continents were selected for their natural beauty, attractive accommodation, abundant charm, and their historical or artistic treasures. The trip begins in the high-class ski resorts and castles of Europe, wending its way to the lush resorts and archaeological pearls of the Mediterranean, where one can breathe history. Onward we trek to spectacular safari sites in the national parks of Africa, to the jewels of antiquity in the Middle East, the sun-drenched beaches of Southeast Asia and Polynesia, onward and upward to the planet's highest mountaintops, finally landing in the Americas for expeditions to the Caribbean, Florida Keys, the Rocky Mountains, California, and the ruins of ancient Amazonian civilizations.